The Rare Malignancy of the Hepatobiliary System: Ampullary Carcinoid Tumor - Mustafa Ozsoy; Yucel Ozsoy; Aras Emre Canda; Olcay Ak Nalbant; Fatih Haskaraca (Case Reports in Medicine)
Introduction. Carcinoid tumors are low-grade tumors originating from endoderm and mostly involving the gastrointestinal system. However; they may be seen in any site within the gastrointestinal system. Case Presentation. A 69-year-old female patient. The results of blood tests were observed to be consistent with obstructive jaundice. A mass appearance was not encountered on tomographic examination. Papilla that was tumor-like macroscopically was seen in the second part of the duodenum in diagnostic endoscopy. Pylorus—preserving pancreaticoduodenectomy surgical procedure was applied. On pathological examination of the mass, a tumoral mass was detected in ampulla vateri localization, 1.5 × 1 × 0.8 cm in size, which, in immunohistochemical staining, was evaluated as a neuroendocrine tumor. Also, Metastasis was observed. Conclusion. The rarest type of carcinoid tumor is ampullary located carcinoid tumor, and tumor size is not a reliable indicator for tumor aggressivity in ampullary carcinoid tumors.